Ontological and epistemological approaches to physical activity and sport in the thought of Plato and Aristotle: philosophical dialogues between the past, present and future - Andrii Synytsia; Roman Rymyk; Lyubomyr Malanyuk; Oleksandr Leshchak (Clío, 2025)
The main objective of this research is to examine the ontological and epistemological dimensions of sport activity in the philosophical thought of Plato and Aristotle, exploring how these universal thinkers integrated gymnastic and athletic practices in their systems of thought. From this objective arose some questions of interest, such as: In what way does gymnastics, together with music, constitute an essential educational element in the political-pedagogical project developed in the Republic? Or in what sense does the pentathlete represent a model of virtue and beauty that illustrates the doctrine of the Aristotelian middle ground? The results obtained allow us to conclude that, in philosophical terms, when it is possible to link conceptual rigor with practical relevance, the philosophy of sport can reclaim its primordial place as a tool for transforming sporting reality and not only as an interpretative exercise. As the rereading of Plato and Aristotle suggests, the real triumph is not in beating others, but in turning each stage of being into a gymnasium for the soul.